2009
DOI: 10.3174/ajnr.a1561
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Follow-Up of Stent-Only Therapy for Acute Intracranial Vertebrobasilar Dissecting Aneurysms

Abstract: BACKGROUND AND PURPOSE:Little has been known about the clinical and angiographic follow-up results of stent-only therapy for intracranial vertebrobasilar dissecting aneurysms (VBDA). The purpose of this study was to evaluate the feasibility, safety, clinical, and angiographic follow-up of stent-only therapy for VBDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 35 publications
3
105
1
8
Order By: Relevance
“…It is well known that stent placement decreases wall shear stress in the aneurysm wall in proportion to the number of overlapping stents. 21,22 As in many previous case studies, 4,5,9,[23][24][25][26] this study showed promising results for the use of multiple overlapping stents, with or without coiling, in the treatment of VBDAs. Newly developed flow diverters, which have far less porosity than conventional neurovascular or coronary stents, may play a decisive role in reconstructive treatment of VBDAs.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…It is well known that stent placement decreases wall shear stress in the aneurysm wall in proportion to the number of overlapping stents. 21,22 As in many previous case studies, 4,5,9,[23][24][25][26] this study showed promising results for the use of multiple overlapping stents, with or without coiling, in the treatment of VBDAs. Newly developed flow diverters, which have far less porosity than conventional neurovascular or coronary stents, may play a decisive role in reconstructive treatment of VBDAs.…”
Section: Discussionsupporting
confidence: 48%
“…The patient showed an enlarged dissecting aneurysm on follow-up angiography and was re-treated with IT, as previously reported. 5 The other received a single stent with coiling for a VBDA that involved the PICA origin; SAH recurred in this patient 3 days after treatment. The patient did not receive follow-up angiography due to poor condition and subsequently died.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations